Effect of Environmental Education Based on Transformational Learning Theory on Perceptions towards Environmental Problems and Permanency of Learning - Uyanık, Gökhan (International Electronic Journal of Environmental Education, 2016)
The purpose of this research is to determine effect of environmental education based on transformational learning theory on primary school teacher candidates’ perceptions towards environmental problems and permanency of learning. Experimental design with pretest-posttest control group have used in this study. The study group of this research consist of 66 teacher candidates who are continuing their education in fourth grade of Kastamonu University Education Faculty Primary School Teacher program in two different sections in 2014-2015 academic year fall term. One of the section is selected as experiment group (N=32) and the other section is selected as control group (N=34) with random assignment method. Environmental problem knowledge test, responsibility behavior scale to environment and the scale of attitude towards environmental problems used as data gathering tools. In order to compare average scores of the groups, t-test have used for independent groups. According to findings, there is a statistically significant difference between experiment and control groups’ knowledge and permanence test in favor of experiment group. Also there is a statistically significant difference between experiment and control groups’ responsibility scale and attitude scale scores in favor of experiment group.
Keywords: Attitude; environment; permanence; transformational learning; 13. Climate action; 4. Education; 3. Good health